Restricted limits on natural functions with arithmetical graphs - Mycka, Jerzy (Revista Colombiana de Computación, 2003)
In this paper we consider the process of defining natural functions by the operation of in nite limit F(x) = limy!1;y2A f(x; y) (also limes inferior and limes superior are taken into account). But two restrictions are assumed: the given natural function f has a graph belonging to some stage of an arithmetical hierarchy, the index of a limit runs only through a given arithmetical subset A of natural numbers. We investigate the arithmetical class of the graph of the function F, where the respective classes of the graph of f and the set A are known. The corollary for the Turing degrees of F is formulated. Keywords: Theory of computation, Innite limits.